The Moderating Effects of Organisational Culture on the Relationship Between Leadership Style and Employee Commitment to Change of Public Sector in Yemen - Gelaidan, Hamid Mahmood Hamid (2012)
Employee commitment to change is a crucial factor of a successful change process that can be enhanced by having effective leadership and supportive organisational culture. The present study was designed to examine the relationship between leadership style and employee commitment to change with organisational culture as a moderating variable. The study was carried-out in public sector in Yemen. The study used transformational and transactional model of leadership to determine employee commitment to change. A quantitative approach was mainly conducted in this study. In order to achieve the main objectives of this study, data were collected from employees of public sector in Yemen. Hierarchical regression analysis was then conducted to examine the moderating effects of the organisational culture on the relationship between leadership style and employee commitment to change dimensions. The results from the regression analysis revealed that transformational and transactional leadership were positively associated with all the dimensions of employee commitment to change; namely affective, continuance and normative. Moreover, the findings showed that transactional leadership had stronger effect on the employee commitment to change compared to transformational leadership. Furthermore, the results also showed that organisational culture plays an important role, which it moderated the relationship between leadership style and employee commitment to change. The study may contribute to the body of knowledge on the change management, and on both leadership and organisational culture perspective. Furthermore, the originality of the research lies in the change management area particularly on the human elements. It is also provided comprehensive practical recommendations for organisations, employees, and leaders to guide them to manage change successfully